A Proposed Quality Improvement of Delivery Services at PT Pos Indonesia Using Importance-Performance Analysis and Kano Model - Silitonga, Roland Y. H.; Tindaon, Phila Delphia; Indriati, Ellen; Martina, Inge (The Indonesian Institute of Science and Technology Research, 2024)
PT Pos Indonesia, a courier service company, contends with a notably low market share, as indicated by Top Brand data reflecting market proportions over the past five years in Indonesia. This decline in market share is predominantly attributed to subpar service quality. Hence, there is a pressing need to scrutinize PT Pos Indonesia to enhance its service standards for consumers and discern the service attributes requiring maintenance and prioritized improvement. This study employs the IPA (Importance Performance Analysis) and Kano method, both of which complement each other synergistically. IPA seeks to unearth insights into service factors influencing customer satisfaction and loyalty, while the Kano model categorizes service attributes based on their capacity to meet customer needs effectively. Additionally, the Kano model identifies areas warranting attention or enhancement, which can augment customer satisfaction. The analysis reveals four attributes classified as defenseless strategy points and one attribute deemed a chronic issue through the amalgamation of IPA and Kano model findings, thereby informing decisions to enhance performance.